2010
DOI: 10.5005/jcdp-11-2-85
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Abscess Due to an Unusual Nail-Biting Habit: A Case Report

Abstract: Aim: Nail-biting is one of the most frequent deleterious oral habits in children. It can result in systemic diseases or oral traumatic lesion. This report describes a case of gingival abscess in a child due to a fingernail-biting habit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“… different foreign bodies have been described to be associated with the development of a periodontal abscess, for example: an orthodontic elastic ; a piece of dental floss ; a dislodged cemental tear ; a piece of a toothpick ; or pieces of nails in subjects with nail‐biting habits . The term ‘oral hygiene abscesses’ has been proposed for abscesses caused by the impaction of foreign bodies that are oral hygiene aids . the root surface may be altered by different factors: perforation by an endodontic instrument ; cervical cemental tears ; external root resorption ; an invaginated tooth ; or a cracked tooth . …”
Section: Abscesses In the Periodontiummentioning
confidence: 99%
See 3 more Smart Citations
“… different foreign bodies have been described to be associated with the development of a periodontal abscess, for example: an orthodontic elastic ; a piece of dental floss ; a dislodged cemental tear ; a piece of a toothpick ; or pieces of nails in subjects with nail‐biting habits . The term ‘oral hygiene abscesses’ has been proposed for abscesses caused by the impaction of foreign bodies that are oral hygiene aids . the root surface may be altered by different factors: perforation by an endodontic instrument ; cervical cemental tears ; external root resorption ; an invaginated tooth ; or a cracked tooth . …”
Section: Abscesses In the Periodontiummentioning
confidence: 99%
“…A combination of different factors, such as pulp vitality, the presence of dental caries, the presence of periodontal pockets, the location of the abscess and a careful radiographic examination, should be assessed in detail to reach an accurate diagnosis. other serious oral diseases may also have a similar appearance: osteomyelitis in patients with periodontitis ; squamous cell carcinomas ; a metastatic carcinoma of pancreatic origin ; a metastatic head and neck cancer ; an eosinophilic granuloma ; or a pyogenic granuloma . Therefore, in patients not responding to conventional therapy, a biopsy and histopathological diagnosis should be recommended. self‐inflicted gingival injuries: including trauma of the gingiva with a pencil or with a safety pin , or a nail‐biting habit . The anamnesis is the key factor in the diagnosis of these lesions.…”
Section: Abscesses In the Periodontiummentioning
confidence: 99%
See 2 more Smart Citations
“…Nail biting may involve physical consequences such as gingivitis, pinworm infestation, giardia infections and changes in nail appearance. Mental disorders often accompany nail biting, because it provokes reactions such as ridicule, embarrassment, warning and anger [115][116][117] . It has been reported that nail biting is often comorbid with other mental disorders, and 65% of those who bite their nails have an additional stereotypic behaviour 118,119 .…”
Section: Nail-biting Behaviormentioning
confidence: 99%